The Role of Influencers, Entertainment Experience, and User Convenience in TikTok Live Streaming on Purchasing Decisions Mediated by Brand Image at LA’SKINIC - Gusti Agung Wirya Dharma; , Agus Putu Abiyasa (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2025)
The main objective of this study is to fill the gap in the literature by investigating the specific role of entertainment influencers and user convenience in TikTok live streaming on consumer purchasing decisions, taking into account the mediating effect of brand image. This study employs a quantitative approach, with data sources comprising a combination of primary and secondary data. Primary data was collected through the distribution of questionnaires, while secondary data was obtained from previous research journals, news articles, and social media. Data analysis techniques include descriptive and inferential analysis. The data in this study were analyzed using the Structural Equation Model (SEM) method with the assistance of Partial Least Squares (PLS) software. Research findings supported by data indicate that influencers, entertainment experiences, and user convenience have a positive and significant effect on purchasing decisions and brand image. Brand image positively and significantly influences purchasing decisions; however, brand image cannot mediate the influence of influencers on purchasing decisions. Brand image can mediate the influence of experience on purchasing decisions; however, brand image cannot mediate the influence of user convenience on purchasing decisions for LA’SKINIC products.